Control interno de los procesos administrativos del comercial Gran Hogar del cantón Babahoyo. - Mastian Sisa, Leyton Santiago (2022)
The present case study called Internal Control of the Administrative Processes of the Comercial Gran Hogar del Cantón Babahoyo Period 2021, aims to analyze the problem around the shortcomings of the control processes in the company, caused by the weak Implementation of a model of control, leading to a scarce delimitation of functions, as well as describing several of the concepts related to the control model COSO (Committee of Sponsoring Organizations of the Treadway) and its components, necessary for the evaluation of the control processes of the company. According to COSO, Internal Control is designed to provide a reasonable degree of assurance regarding the achievement of objectives within the following categories: Effectiveness and efficiency of operations, Reliability of financial information, Compliance with laws, regulations and standards. that are applicable. Based on the five components of the COSO model, which are mentioned below; the Control Environment, the Risk Assessment, the Control Activities, the Information and Communication, the Supervision or Monitoring, the particularity of each one of them is described and the importance of the same in the correct functioning of the internal control of the company, This description allows the analysis of the control model within the Commercial, evidencing the present shortcomings, which are determined by applying the survey technique to the commercial workers, allowing the evaluation of their results to generate criteria related to the model. control of the company, determining conclusions and recommendations that serve as a guide for the implementation of improvements in the control model.